Erotic Coleridge - Taylor, A. author. aut Link
XI, 220 p.
Keywords: Erotic Coleridge charts Coleridge's prolific creation of love poems from early flirtatious verse to poems about marital incompatibility, the blank faces of young women fearing for their reputations, the obliterating seductions of young women, the exaltation of falling in love, the spoken and sung voices of women, the pain of jealousy, and late meditations on how to live with the waning of love. In his prose he responds to Parliamentary debates about punishing adulteresses and gives advice about how marriage can warp the soul. In his sensual exuberance and his ethics of reverencing the individuality of other persons, Coleridge attends closely to the lives of women.